Intermittency in Voyager’s Magnetic Field Beyond the Heliosphere - L. Y. Khoo; G. Livadiotis; D. J. McComas; M. E. Cuesta; J. S. Rankin (The Astrophysical Journal)
As the two Voyager spacecraft traveled beyond the heliosphere, they encountered a magnetic field environment that had never been observed before. Studies have attempted to characterize this new regime by examining the magnetic field intermittency. This is typically done by fitting the optimal kappa distribution function and interpreting its q -statistics to characterize the magnetic field increments. Using this approach, recent findings concluded that beyond a certain distance, the magnetic field increments in the very local interstellar medium (VLISM) follow Gaussian statistics, unlike those both inside the heliosphere and in the region just beyond the widely accepted heliopause location, raising questions about the heliopause identification. This study explores this issue in detail by (1) optimizing the derivation of the distribution function, (2) examining whether and how the results depend on increment windows and time periods, and (3) determining the statistical behavior of the examined time series. Using magnetic field measurements from Voyager 1, we present two independent techniques and introduce a statistical framework to systematically analyze the distributions of magnetic field increments. Contrary to previous findings, we find that magnetic field increments in the VLISM do not follow a Gaussian distribution (κ → ∞) and instead are in the non-Gaussian range of kappa values (3–7, when analyzed on a 30 days statistical period). We further demonstrate how erroneous, statistically induced results can arise that mimic Gaussian-like results when mixing different structures in such analyses. Our results show that Voyager 1 still travels in the intermittent magnetic field environment of the VLISM.